2007
DOI: 10.1300/j013v46n02_08
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Spirituality in Sustaining the Psychological Well-Being of HIV-Positive Black Women

Abstract: Historically, spirituality has been an instrumental component to the survival of Black women. In an era when the HIV epidemic disproportionately compromises their health, it is imperative to explore spirituality's role in sustaining the psychological health of Black women living with HIV. This study examined the relationship between spirituality and self-reported depression among Black women living with HIV. A sample of 308 HIV-positive Black women were recruited from HIV/ AIDS clinics in the Southeastern Unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 43 publications
4
27
0
Order By: Relevance
“…This finding complements not only literature from other studies examining women diagnosed with HIV9,40 but also with other validated measures of religion and spirituality 14. This corroboration is promising for the subsequent validation of the HEALS.…”
Section: Discussionsupporting
confidence: 82%
“…This finding complements not only literature from other studies examining women diagnosed with HIV9,40 but also with other validated measures of religion and spirituality 14. This corroboration is promising for the subsequent validation of the HEALS.…”
Section: Discussionsupporting
confidence: 82%
“…The protective role of spirituality among the immigrant women in this study is consistent with a body of literature on immigrants and other groups (Braxton et al, 2008;Connor, 2012;Koenig, 2012;Lake, 2012;Rosmarin, Wachholtz & Ai, 2011;Smith, Webber & DeFrain, 2013;Temane & Wissing, 2006). Shaw, Joseph and Linley proposed that the beneficial role of spirituality and religion in mental health is generated through strong values and beliefs that enhance meaning of life, increase social support, and promote acceptance of difficulties (Shaw, Joseph & Linley, 2005).…”
Section: Discussionsupporting
confidence: 88%
“…The women's faith in Allah and His benevolence helped them to make a positive evaluation of life events; women hoped that, due to their prayers, Allah would change the behavior of their husbands one day. Braxton, Lang, Sales, Wingood, and DiClemente (2007) also noted in their study that spirituality was strongly associated with positive and optimistic feelings in stressful situations. Paradoxically, some studies have shown that a heavy reliance on spiritual coping therapies may undermine women's efforts in taking realistic steps to solve the underlying problem and could also contribute to delay in seeking institutional support (Maman et al, 2009).…”
Section: Discussionmentioning
confidence: 81%